Correction: Characteristics of people with epilepsy and Neurocysticercosis in three eastern African countries-A pooled analysis. - Dominik Stelzle; Veronika Schmidt; Luise Keller; Bernard J Ngowi; William Matuja; Gabrielle Escheu; Peter Hauke; Vivien Richter; Emilio Ovuga; Bettina Pfausler; Erich Schmutzhard; Action Amos; et al. (PLoS Neglected Tropical Diseases)
[This corrects the article DOI: 10.1371/journal.pntd.0010870.].